Metaphonological awareness instruction: acrolectal English for tertiary students / Bromeley Philip and John Francis Noyan - Philip, Bromeley; Noyan, John Francis (2019)
The study was aimed at implementing a metaphonological awareness instructional approach for pronunciation teaching and learning of suprasegmental features of English sounds namely, the schwa vowel and the catenation or linking features. The main focus of the study was to promote the use of acrolectal English in tertiary institutions in Malaysia so as to encourage students to gain native-like or near-native fluency particularly in terms of phonology. The study employed an ethnographic design, specifically using a qualitative case study method, which involves 5 participant undergraduates at a public university in Sarawak. The teacher-student scaffolding episodes were qualitatively evaluated in a context of teaching and learning of selected aspects of suprasegmental features of English sounds. The instruction was found to be positive in enhancing the students’ metaphonological awareness of acrolectal English pronunciation.